Inflammatory Responses to Acute Spinal Loading - Beharriell, Tianna (Université d'Ottawa / University of Ottawa, 2018)
Currently, low back disorder (LBD) research focuses primarily on mechanical variables to assess whether acute or cumulative task demands exceed the capacity of the tissue; however, it is important to assess how other non-mechanical variables affect tissue capacity in a time-dependent manner. The current investigation sought to explore physiological responses to an acute lifting task (similar to a typical assembly line task), as lifting has been implicated as a risk factor in the development of LBDs. Twelve participants completed two experimental sessions of two hours of repetitive symmetrical lifting from floor to knuckle height under a low force, high repetition condition (LFHR; box weighted at 5% maximum lifting strength, five lifts per minute) and a high force, low repetition condition (HFLR; 25% maximum lifting strength, one lift per minute), such that the external biomechanical work was equivalent between conditions. These sessions were completed one week apart, with full-body motion capture and ground reaction forces measured throughout. Systemic inflammation was assessed with blood sampling at baseline, 0, 4 and 24 hours post-lifting on both days, and samples were assayed using an ELISA for interleukin 6 (IL-6) and interleukin 8 (IL-8). Participants also completed psychological questionnaires including the Tampa Scale for Kinesiophobia-General (TSK-G), Pain Catastrophizing Scale, Visual Analogue Scale (VAS, participants 1-4) and Borg CR-10 Scale of Exertion (participants 5-12). There was a significant main effect of time on both IL-6 and IL-8 (Baseline, 0, 4, 24 hours), as well as interaction effects of condition (HFLR and LFHR) and time. The LFHR condition caused greater inflammation in both IL-6 and IL-8 at 0 and 4 hours post-lifting, likely due to significantly higher cumulative spinal loading in this condition. Significant correlations between body fat percentages, peak and cumulative loading were found to exist in both the LFHR condition and the HFLR condition, lending strength to the hypothesis that some of these measures may be able to predict physiological responses to acute stresses, and subsequently, risk of acute injury.
Keywords: inflammation; spinal loading; acute stress; physiology; biomechanics; ergonomics; kinesiology; human kinetics